Factors of Adoption Intention for Near Field Communication Mobile Payment - Sharidzaly Busu; Norisan Abd Karim; Haryani Haron (Institute of Advanced Engineering and Science, 2018)
Near field communication mobile payment (NMP) is simple to use and beneficial to consumers, yet its adoption among consumers in Malaysia is still at the beginning stage and the adoption rate is relatively lower compared to other countries in the world. The aim of this study is to identify factors that affect the adoption intention of NMP among consumers in Malaysia, by using Faculty of Computer and Mathematical Sciences (FSKM), UiTM Shah Alam as the case study for this research. The quantitative data analysis approach is used in this study. There were 150 questionnaires analyzed using the SPSS. This research identified three factors that affect the adoption intention of NMP which are perceived usefulness, perceived cost and compatibility. By understanding the factors affecting the intention to adopt NMP, financial technology companies can focus to provide the solutions according to market interest, needs and readiness.